SUSTAINABLE DEVELOPMENT OF GENDER EQUALITY IN THE REPUBLIC OF UZBEKISTAN (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
Gender is the socially used definition of women and men. This concept does not mean the biological characteristics of women and men. On the contrary, the concept of gender is based on the idea of the tasks and functions of women and men in society, public and private life.